The Influence of Paired Passing Exercises on the Enhancement of Forearm Passing Skills Among Elementary Volleyball Extracurricular Students - Bayu Budiman; Bujang (Universitas Negeri Semarang, 2025)
This study aims to determine the effect of paired passing drills on the improvement of forearm passing skills among elementary school students participating in volleyball extracurricular activities at Public Elementary School Pondok Ranggon, East Jakarta. The research method used was an experimental approach with a one-group pre-test and post-test design. A total of 30 students were selected as subjects. Data were collected through a forearm pass skill test and analyzed using a paired sample t-test. The results showed a significant increase in students’ forearm passing abilities after participating in the paired passing training, with a mean improvement of 10.9 points (t = 11.03, p < 0.05). These findings suggest that the paired passing method is effective in enhancing the fundamental volleyball skills of young learners.